Métodos de inoculação, reação de acessos e herança da resistência do meloeiro a Rhizoctonia solani - Melo, Dalila Regina Mota de (Universidade Federal Rural do Semi-Árido, 2014)
Many problems occur in melon, among them the diseases caused by soil born fungi such as Rhizoctonia solani. The use of resistant cultivars is a strategic measure in the integrated management of diseases. In order to obtain cultivars with resistance, it is necessary to identify sources of resistance in germplasm available and know the genetic control of resistance. Objectives of this study were to evaluate two methods of inoculation, the reaction of melon accessions to R. solani and to study the inheritance of resistance of melon to Rhizoctonia canker. The experiments were conducted at the Rural Federal University of the Semi-arid. In the first experiment, two methods of inoculation (sandy-organic and toothpick) of R. solani in melon were evaluated. The method toothpick was the most efficient in discriminating the reaction of melon accessions and virulence of isolates of R. solani. In the second experiment, the reaction of 42 hits and 3 melon hybrids to three isolates of R. solani was evaluated. The C-AC-03 and 'Olympic' accessions were identified as moderately resistant. In the third experiment, we investigated the inheritance of resistance of 'Olympic' in crosses with the susceptible parents 'Mabel' and C-AC-11. A major gene with both additive and dominant effects and polygenes with additive effects controlled the resistance to Rhizoctonia canker melon
Inoculation methods, reaction of accessions and inheritance of resistance of melon plant to Rhizoctonia solani
Keywords: Cucumis melo; Pathogens of soil; Germplasm; Genetic control; Polygenes; Cucumis melo; Patógenos de solo; Germoplasma; Controle genético; Poligenes; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA